Contribuições da monitoria em clubes de ciências para o aprimoramento pessoal e cognitivo do aluno-monitor - Costa, Gian Giermanowicz (2019)
The research presents as scenario the Science Clubs, non-formal learning spaces that through research, debate and teamwork, scientific thinking is developed. The Science Club target of this investigation is maintained by a partnership between a University in South of Brazil and a network of Basic Education schools. There are two groups participating in these spaces: (1) teachers (Higher and Basic Education) and (2) students, divided into three subgroups: a) undergraduate students who act as monitors; b) Basic Education alumni from the Science Club, who also act as monitors; c) Primary School students who participate in weekly activities - planned by teachers and monitors - opposed to their school activities. The subjects of this research are the alumni of the Science Club who act as monitors. The present study had as objective to understand the influence of the monitoring in Science Club in order to potentiate the integral formation of student-monitor. For the purpose of responding to the research objectives, the following instruments were used to collect data: letter of intention of the students-monitors, observation records of the researcher in field journal, group interview with students-monitors, online forum and semi-structured interviews with the legal heads of students-monitors. The material from these instruments was analyzed through Discursive Textual Analysis, described by Moraes and Galiazzi (2011), with the aim of producing new understandings on the discourses studied. The categories that emerged from the Discursive Textual Analysis process were: living category: self and others, existence category: protagonist student attitude and doing category: plan, execute and deal with unforeseen. Each category collaborated to comprehend the contributions of monitoring in Science Clubs in the improvement of cognitive aspects, intra- and interpersonal, necessary for the 21st century individual to be established in society.